SIMULATION OF ORTHODONTIC TOOTH MOVEMENT PRODUCES BY A SECTIONAL RETRACTION SPRING - AHMAD KIRANA (NIM : 13105019); Pembimbing : Dr. Ir. Rachman Setiawan, FIRMAN
A tooth is secured to the bone by fibrous connective tissue. A tooth does not always occupy on the right position. Incorrect position of tooth is studied in orthodontic. Orthodontist will apply a spring to correct tooth position. Type of spring will determines magnitude of force and moment are applied in a tooth. Force system consisting of force and moment, and their point of application will determine type of tooth movement. However, tooth movement value still cannot be known easily. In this research, tooth movement is simulated with simple two-dimensional analytical approach. Soft connective tissues around the tooth are assumed linear elastic, homogeneous, and isotropic. Force system which is applied to the tooth causes tooth displacement and deformation of soft connective tissues. Its magnitude is calculated analytically. The deformation causes biologic response that in terms moves the tooth. Tooth movement result of biologic response is simulated numerically by looping the process of tooth displacement result of force system. Parameters of tooth that affect tooth movement are length of root, center of resistance, diameter of tooth, mechanical properties of tissue, and thickness of fibrous connective tissue that support a tooth. Simulation of tooth movement has been made successfully by accumulating tooth displacement due to the force that has decreased. The simulation was shown in animation. Making animation program of tooth movement can make orthodontist or patient easier to know result of application of spring to the patient.